Studi proses pembuatan biodiesel dari minyak kelapa (coconut oil) dengan bantuan gelombang ultrasonic - Sri Kembaryanti Putri; Supranto Supranto; Rahman Sudiyo (Jurnal Rekayasa Proses, 2012)
Biodiesel is produced by methanolysis of various vegetable oils such as coconut oil, palm oil, seed oil, soybean oil, etc. Coconut oil has the potential as a raw material for making biodiesel due its abundant availability. The use of the ultrasonic waves can increase conversion and reaction rate. The objective of this study was to study the effect of the use of ultrasonic waves on the transesterification of coconut oil, the ratio of reactants, catalyst concentration, and activation of methanol on the reaction conversion. Sodium hydroxide catalyst with a specific weight was dissolved in methanol with a certain volume. After dissolvtion was completed, the reactants including coconut oil with a certain volume were put into the reactor, and reaction was then started. Samples were taken every 10 minute intervals for analysis of fatty acids. The reaction was stopped after 60 minutes. Furthermore, biodiesel was separated from glycerol and purified. Experimental results showed that transesterification of coconut oil could be improved with the help of ultrasonic waves. The obtained conversion was 4 times higher (85,66%) than the conversions generated in the conventional process (20,15%) The process was done in the same condition which was the ratio of reactants of 5 mgek methanol / mgek oil, catalyst 1% by weight oil and the initial reaction temperature of 60C. The greater the ratio of methanol-oil equivalent, the higher reaction conversion is.